H2O Innovation's PWT introduces new logo and corporate image. Issue 10 (October 2015) - Unknown
Abstract : Canada's H2 O Innovation Inc's Professional Water Technologies (PWT), a specialist in membrane filtration chemicals and membrane forensics services, has revamped its corporate image and has created a new company logo.